2001
DOI: 10.1116/1.1387456
|View full text |Cite
|
Sign up to set email alerts
|

New phase formation of Gd2O3 films on GaAs(100)

Abstract: A fluorite-related phase of Gd 2 O 3 , with a tetragonal unit cell of aϭ5.65 Å and cϭ5.37 Å, was attained in this study. The new phase was found either in a thin Gd 2 O 3 film ͑ϳ18 Å͒, which was epitaxially grown on GaAs͑100͒, or in a disordered ͑by mild Ne ϩ -ion sputtering͒ and recrystallized ͑by UHV annealing͒ thin cubic ␣-Gd 2 O 3 film. The structural characteristics of the new oxide films were studied using in situ reflection high-energy electron diffraction, secondary-electron imaging, and single-crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Gadolinium sesquioxide, one of the promising substitutions with a high dielectric constant for SiO 2 in ultra large-scale integration (ULSI) [3,4], has attracted much attention recently. The studies on gadolinium oxide are focus on structures [5,6], interfacial reaction with silicon [7,8], physical properties [9,10], and as a passivation of GaAs [11,12]. Relatively, the photoluminescence (PL) characters of gadolinium oxide have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Gadolinium sesquioxide, one of the promising substitutions with a high dielectric constant for SiO 2 in ultra large-scale integration (ULSI) [3,4], has attracted much attention recently. The studies on gadolinium oxide are focus on structures [5,6], interfacial reaction with silicon [7,8], physical properties [9,10], and as a passivation of GaAs [11,12]. Relatively, the photoluminescence (PL) characters of gadolinium oxide have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Getting MOSFETs even of this quality also requires that there is no air-break between growth of the GaAs and the oxide, so that complex multichamber MBE systems are necessary. Several follow-up structural analyses of Gd 2 O 3 /GaAs(100) [11][12][13] revealed that perfect strained epitaxy only occurs in the first few layers.…”
mentioning
confidence: 99%
“…Getting MOSFETs even of this quality also requires that there is no air-break between growth of the GaAs and the oxide, so that complex multichamber MBE systems are necessary. Several follow-up structural analyses of Gd 2 O 3 /GaAs(100) revealed that perfect strained epitaxy only occurs in the first few layers. When the oxide film thickness exceeds ∼3 nm, the Gd 2 O 3 film starts to relax by generating misfit dislocations, so that the film is no longer perfectly epitaxial .…”
mentioning
confidence: 99%
“…Moreover, single crystal pure rare earth oxides (such as Gd 2 O 3 and Y 2 O 3 ) have been grown epitaxially on GaAs 12 . A detailed study on the interface of Gd 2 O 3 /GaAs has resulted in a new structure 21 of Gd 2 O 3 with a new stacking sequence 22,23 , which is similar to that of the underlying GaAs. Unlike SiO 2 grown on Si, which is amorphous, the heterostructure of Gd 2 O 3 / GaAs is all single crystal.…”
Section: (C) Single Crystal Gd 2 O 3 On Gaas and Interfacesmentioning
confidence: 99%